Prevalence of intracardiac thrombi under phenprocoumon, direct oral anticoagulants (dabigatran and rivaroxaban), and bridging therapy in patients with atrial fibrillation and flutter - Zylla, Maura Magdalena; Pohlmeier, Mara; Heß, Alexander; Mereles, Derliz; Kieser, Meinhard; Bruckner, Thomas; Scholz, Eberhard P.; Zitron, Edgar; Schweizer, Patrick Alexander; Katus, Hugo; Thomas, Dierk (The American journal of cardiology, 2014)
Direct oral anticoagulants (DOACs) are effective for stroke prevention in nonvalvular atrial fibrillation (AF). Cardioversion (CV) is frequently performed in patients with AF or flutter. To further explore the safety profile of DOACs in the context of CV, we sought to assess the prevalence of intracardiac thrombi under DOAC therapy in comparison with treatment with vitamin K antagonists. A total of 672 transesophageal echocardiograms performed in 643 patients with a history of nonvalvular AF were analyzed. The median CHA2DS2-VASc score was 4. Cases were stratified according to anticoagulation with dabigatran (n = 79), rivaroxaban (n = 122), phenprocoumon (n = 180), or bridging therapy (n = 287). In a subgroup analysis, only patients receiving phenprocoumon with an international normalized ratio ≥2 on the day of the investigation or on DOAC therapy for ≥3 weeks were considered. The prevalence of intracardiac thrombi under phenprocoumon was significantly higher than under DOACs (phenprocoumon, 17.8%; all DOACs, 3.9%; dabigatran, 3.8%; rivaroxaban, 4.1%) and showed no significant difference to bridging therapy (12.5%). In patients with sufficient short-term anticoagulation, similar differences between DOAC and phenprocoumon groups were observed (phenprocoumon, 18.4%; all DOACs, 3.8%; dabigatran, 0%; rivaroxaban, 6.6%). The influence of anticoagulation medication on thrombus rates was confirmed after adjusting for baseline intergroup differences regarding left atrial size and CHA2DS2-VASc score. In conclusion, the prevalence of intracardiac thrombi was lower under DOAC therapy than under phenprocoumon in this high-risk patient cohort. Safety of CV during DOAC treatment requires further prospective evaluation.